Blurring Geographies: Resignification Processes among Evangelical Indigenous Communities in the Borderlands of Bolivia, Chile, and Peru - Mansilla, Miguel Angel (2025)
This article aims to analyze the border and cross-border mobility of indigenous evangelical (Protestant and Pentecostal) communities—specifically Aymara and Quechua—and its influence on the processes of ethnic (indigenous), national (Bolivian, Chilean, and Peruvian), and religious resignification in the tri-border regions. We begin from the epistemological premise that borders are relational spaces, culturally constructed, historically situated, and globally affected. Indeed, cross-border mobility is an inherent social phenomenon. We specifically refer to the tri-border space formed by Bolivia, Chile and Perú, as an ancestral space whose cultural significance predates the formation of nation-states, which initially considered these areas as uninhabited. Methodologically, this is a study based on historical and multi-sited ethnography. This approach allowed us to examine Protestant evangelical missions that viewed Indigenous peoples as a civilizational field, which Pentecostalism would later reinterpret as a field for conversion. Among the main findings is that the conversion of Aymara individuals to evangelical religion led to the emergence of Aymara Pentecostal leaders who revitalized Andean communities through Pentecostal practices, continuously traversing transborder spaces. Thus, in these regions, Pentecostal church function as a transversal religious force—intersecting with Catholicism, Andean spirituality, and evangelicalism—thus blurring cultural geographies and contributing to the mobility and resignification of transborder Indigenous communities.